Advances in Pancreatic Cancer - Rodrigo, Luis (IntechOpen, 2018)
Pancreatic cancer is a growing source of cancer-related death and has poor survival rates, which have not improved in the last few decades. Its high-mortality rate is attributed to pancreatic cancer biology, difficulty in early diagnosis, and lack of standardized international guidelines in assessing the pancreatic masses. This book aims to provide an update in the current state of play in pancreatic cancer diagnosis and to evaluate the benefits and limitations of the available diagnostic technology and therapy. The main modalities for diagnosis are imaging with HCT, MRI, USE, and PET. Some chapters review the improvements in the techniques used. Timely and accurate diagnosis of pancreatic cancer can lead to improve in the current poor outcome of this disease.